Construction of homogeneous climatic regions by combining cluster analysis and L‐moment approach on the basis of Reconnaissance Drought Index for Pakistan. (16th July 2019) - Ullah, Hamd; Akbar, Muhammad; Khan, Firdos
Abstract: Drought is a natural hazard which has slow onset and assessment of its vulnerability is important for water resources management and sustainable development particularly in the most vulnerable areas to climate change and its worse impacts. Pakistan is facing acute water scarcity and regionalization of drought is a pre‐planning strategy for coping the severe condition of water management in the country. This study is conducted to identify homogenous climatic regions (HCRs) with respect to drought condition based on Reconnaissance Drought Index using climate data of 55 metrological stations across Pakistan. For this purpose two statistical methods, cluster analysis and L‐moments technique were used. First, cluster analysis was performed using site characteristics of the stations which identified five homogenous groups. Second, two statistical measures that is, discordancy measures and heterogeneity measure were implied after some regional adjustments, to satisfy the homogeneity of the homogenous groups developed in step one based on at‐site statistics of the stations using L‐moments technique. These statistical measures established validity of five homogeneous climatic regions for Pakistan. Third, to assess these HCRs several results using site characteristics and climate data of the stations were calculated which show that elevation has key role in the rainfall pattern and aridity of the regions. According to the results, there is high variability among these regions with respect to water recourses. First two regions consists most elevated areas with enough rainfall and glacier. Regions (3) and (4) include most vulnerable and drought‐prone areas of Sindh and Baluchistan provinces while Region (5) has enough rainfall in monsoon season. This study findings will help in adaptation, mitigation and future's planning regarding climate, water resources management, monitoring droughts and its projections etc. in different areas and fill the gaps in existing literature in Pakistan. Abstract : Schematic presentation of the methodology adopted for construction of homogenous climatic regions in Pakistan.